Th1 regulatory events by infectious pathogens, herpes zoster and herpes simplex viruses: prospects for therapeutic options for atopic eczema - Horiuchi, Yasuhiro (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2022)
Infections caused by viral and bacterial pathogens are typically perceived as harmful, such as in cases of herpes zoster and herpes simplex virus infections. However, clinical observation of an improvement in atopic skin lesions upon herpes virus infection has been noted, particularly at the site of varicella and Kaposi’s varicelliform eruption. Th1 immune cells and cytokines, mobilized and induced for protection against infectious pathogens, are expected to improve Th2 dominant atopic symptoms. This study focuses on Th1 immunoregulatory events mediated by infectious pathogens, particularly herpes viruses. Immunoregulatory events induced by herpes viruses may have a potential therapeutic value for treating atopic eczema.